Implementasi Kebijakan Penanganan Penyelundupan Pakaian Bekas di Provinsi Riau, Indonesia - Yaneski, Arifa Filza; Susiatiningsih, Hermini; Basith Dir, Andi Akhmad (Journal of International Relations, 2018)
This research aims to describe about secondhand clothes smuggling and implementation ofLegislation Number 7 of 2014 as Indonesia’s government effort to overcome thesecondhand clothes smuggling in Indonesia, specifically in Riau. This research is adescriptive research guided by transnational crime concept by United Nation Conventionagainst Transnational Organized Crime and a public policy theory by Van Meter and VanHorn called a Model of Policy Implementation Process. This theory describe that a policyimplementation is affected by five factors; policy’s standardization, resource, agent’scharacteristic, and society conditions (social, economy, and politics). This research is aqualitative research by using interview and literature studies as the data source. The resultof this research are some factor explications about standardization of Legislation Number7 of 2014 affecting the policy implementation and also there are some influences fromeconomic condition in Riau that cause any resistance about the policy.